Altered Hippocampal Neurogenesis and Amygdalar Neuronal Activity in Adult Mice with Repeated Experience of Aggression - Smagin, Dmitry A.; Park, June-Hee; Michurina, Tatyana V.; Peunova, Natalia; Glass, Zachary; Sayed, Kasim; Bondar, Natalya P.; Kovalenko, Irina N.; Kudryavtseva, Natalia N.; Enikolopov, Grigori (Frontiers in Neuroscience, 2015)
The repeated experience of winning in a social conflict setting elevates levels of aggression and may lead to violent behavioral patterns. Here we use a paradigm of repeated aggression and fighting deprivation to examine changes in behavior, neurogenesis, and neuronal activity in mice with positive fighting experience. We show that for males, repeated positive fighting experience induces persistent demonstration of aggression and stereotypic behaviors in daily agonistic interactions, enhances aggressive motivation, and elevates levels of anxiety. When winning males are deprived of opportunities to engage in further fights, they demonstrate increased levels of aggressiveness. Positive fighting experience results in increased levels of progenitor cell proliferation and production of young neurons in the hippocampus. This increase is not diminished after a fighting deprivation period. Furthermore, repeated winning experience decreases the number of activated (c-fos positive) cells in the basolateral amygdala and increases the number of activated cells in the hippocampus; a subsequent no-fight period restores the number of c-fos-positive cells. Our results indicate that extended positive fighting experience in a social conflict heightens aggression, increases proliferation of neuronal progenitors and production of young neurons in the hippocampus, and decreases neuronal activity in the amygdala; these changes can be modified by depriving the winners of the opportunity for further fights.